G243(P) Audit of Paediatric Handovers: SBAR Quality and Length of Handover. (24th May 2017) - Tan, Y; Kotecha, B; Karupaiah, A; Verma, P; Saleem, Z
Abstract : Aims: Handover is an important tool in clinical medical practice. Handovers are the transfer of responsibility for care from a group of doctors to another, alerting the team about sick patients, staffing issues and anticipate any problems that may arise. This closed loop audit was performed to assess the length and quality of handovers using the SBAR tool. Methods: This prospective audit collected data using a proforma between May to June 2016. Morning, afternoon, night handovers during the week and weekends were included. The re-audit was performed between October and November 2016. The proforma collected data on start times, finishing times, reasons for delay, members of staff present including consultants and a comment section for notes on that specific handover. At the end of each handover, two doctors receiving the handover were asked to score the quality of SBAR handover in view of structure and clarity and effectiveness for the shift ahead (1- Strongly Agree, 2 Agree, 3- Disagree, 4 Strongly disagree). Results: In May to June 2016, (n=41 handovers) 15 morning handovers, 10 evening handovers and 16 night handovers were assessed. The average time for morning handovers were 26.8 min however the neonatal consultant attendance was 34% (5/15). On re-audit in October and November 2016, (n=25 handovers) 12 morning handovers, 5 afternoon handovers, 5 night handovers and 3 weekend handovers. The average time for morning handovers increased to 30.3 min, however neonatal consultant attendance in morning handovers increased to 75% (9/12). While the handovers on average were still 30 min in length, 20% of handovers either start late or finish late. Overall, more than 85% of handovers the receiving team answered strongly agreed or agreed that SBAR handover was structured with clarity and effectiveness for the upcoming shift. Conclusion: This audit for evaluating length and quality in paediatric handovers identified areas requiring most improvement. Areas for ongoing improvement included introduction of a safety briefing and inclusion of nursing presence within handovers. Further improvement strategies include a handover checklist to include safety brief, staffing levels, highlighting sick patients and encouragement of the SBAR format for trainee assessments.